Ivory and religious statues in the Philippines today - Lucy Vigne (Pachyderm)
From 2009 corrupt officials in the Philippines were reported to have stolen tonnes of African elephant tusks that customs had confiscated in transit from Africa to China. In 2011 a survey found ivory being carved and ivory items sold in Manila (albeit small amounts). In February 2015 a follow-up survey was undertaken. Little had changed in the ivory market and government inspections were not preventing new illegal ivory items from entering the market. The wholesale price of raw ivory had risen slightly from USD 446/kg in 2011 to USD 462/kg in 2015 for average 5-kg (mostly African) tusks. In 2011 there were 20 retail outlets counted with 264 ivory items displayed for sale and in 2015 there were 24 shops with 350 items on display, most of them carved before 1990. Antique outlets displayed most of these items. Figures of Catholic saints predominated, followed by smaller human and animal figurines and jewellery, generally of Chinese or African origin, brought to Manila by members of Filipino diaspora. Prices of pre-1990 ivory items were generally the same as four years earlier. Vendors described how the stolen tusks provided a small flow of ivory for carving new religious figurines. Some new religious statues with ivory, up to 3 m high, were also seen openly on sale to the rich elite in Manila.